Intermediate Latency-Evoked Potentials of Multimodal Cortical Vestibular Areas: Galvanic Stimulation - Kammermeier, Stefan; Singh, Arun; Bötzel, Kai (Frontiers in Neurology, 2017)
Introduction: Human multimodal vestibular cortical regions are bilaterally anterior insulae and posterior opercula, where characteristic vestibular-related cortical potentials were previously reported under acoustic otolith stimulation. Galvanic vestibular stimulation likely influences semicircular canals preferentially. Galvanic stimulation was compared to previously established data under acoustic stimulation. Methods: 14 healthy right-handed subjects, who were also included in the previous acoustic potential study, showed normal acoustic and galvanic vestibular evoked myogenic potentials VEMP. They received 2000 galvanic binaural bipolar stimuli for each side during EEG recording. Results: Vestibular cortical potentials were found in all 14 subjects and grand average bilaterally. Anterior insula and posterior operculum were activated exclusively under galvanic stimulation at 25, 35, 50 and 80ms; frontal regions at 30 and 45ms. Common potentials also found during acoustic stimulation were found at 70ms in frontal regions and 110ms in all involved regions. Conclusions: Galvanic semicircular canal stimulation evokes specific potentials in addition to those also found with acoustic otolith stimulation in identically located regions of the vestibular cortex. Vestibular cortical regions activate differently by galvanic and acoustic input at the peripheral sensory level. Significance: Differential effects in vestibular cortical evoked potentials may see clinical use in specific vertigo disorders.